Design Parameters for Massive Communication Systems Under Energy-Efficient Polynomial Precoder - El-Mashed, Mohamed G.; Alraddady, Fahad; Aldosari, Fahd; Faragallah, Osama S. (IEEE access, 2022)
Massive multiple-input multiple output (MIMO) systems have been introduced as a resolution for next generation cellular systems. The complexity of computing the precoding in massive MIMO is increased. So, studying a scalable precoding in massive MIMO system is a challenge task. In this paper, we propose a scalable precoder based polynomial for multiuser massive MIMO system, where base station (BS) is equipped with antennas that simultaneously communicate user equipments (UEs). This precoder applies matrix polynomial instead of matrix inversion. An energy efficiency (EE) optimization problem is formulated. This paper also studies optimal design parameters, which are the optimal transmit power, active UEs and number of antennas at BS. Mathematical formula for the EE-maximizing parameter estimations was mathematically analyzed with different orders of polynomial precoder. The impact of increasing polynomial orders is studied on the system performance. Comparison between proposed precoding technique and conventional techniques (i.e., zero forcing (ZF) precoder, minimum mean square error (MMSE) precoder and linear precoder) is provided. Results have shown that maximal EE and area throughput are achieved by deploying polynomial precoder in multiuser massive MIMO system. It can achieve better performance compared with conventional techniques. Utilization of polynomial precoder enhances the performance and provides high EE values.